2014
DOI: 10.3109/14767058.2014.923393
|View full text |Cite
|
Sign up to set email alerts
|

Impact of simulation and team training on postpartum hemorrhage management in non-academic centers

Abstract: Simulation and team training significantly improved postpartum hemorrhage response times among clinically experienced community labor and delivery teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 17 publications
1
43
0
3
Order By: Relevance
“…37 Table 4 lists innovations that have been used to recruit, train, and support those who choose to practice in rural settings. 36,[38][39][40][41][42][43][44][45][46][47][48][49] Nearly all of these programs require funding and collaboration with stakeholders such as communities or the government in order to be successful in addressing maternal health disparities in rural populations.…”
Section: Special Articlementioning
confidence: 99%
See 1 more Smart Citation
“…37 Table 4 lists innovations that have been used to recruit, train, and support those who choose to practice in rural settings. 36,[38][39][40][41][42][43][44][45][46][47][48][49] Nearly all of these programs require funding and collaboration with stakeholders such as communities or the government in order to be successful in addressing maternal health disparities in rural populations.…”
Section: Special Articlementioning
confidence: 99%
“…Teamwork training in a simulation setting to improve knowledge, practical skills, communication, and performance in acute obstetric situations Implementation of team behaviors to reduce medical errors and improve patient safety 48,49 the other hand, the extreme joy of participating in births and the continuity of care that doing so offers is an emotion that often sustains FP maternity care providers in their work. There was a strong opinion among workshop attendees that intentionally creating specific professional support around bad outcomes while celebrating the unique joys of providing intrapartum care and sharing this support with learners may help to support FP maternity care providers to continue to practice while inspiring a new generation.…”
Section: Team-based Training and Simulationmentioning
confidence: 99%
“…Teamwork training in a simulation setting improved knowledge, practical skills, communication, and team performance in acute obstetric situations in 7 studies 29 and improved perinatal outcomes in 3 studies. [29][30][31] Obstetric simulation training initiatives have been successfully implemented in rural hospitals in Wisconsin 32 and Oregon 33 with funding from the Health Resources and Services Administration and the Agency for Healthcare Research and Quality, respectively. Many hospitals in our survey reported participating in obstetric quality improvement and patient safety initiatives in partnership with hospital networks, hospital systems, state hospital associations, state health departments, or other private and public partners.…”
Section: Maintaining Skills In Low-birth-volume Settingsmentioning
confidence: 99%
“…Moreover, an intervention study in the United States showed improved response times related to PPH management among experienced clinical teams. This was an important finding, because time delay in identification and treatment of PPH can cause a deterioration of the mother’s condition within minutes [15]. Simulation training could help improve response times.…”
Section: Introductionmentioning
confidence: 99%